Optical properties of antimony-borate glass rods co-doped with Eu3+/Ag+ ions - Czajkowski, Karol; Leśniak, Magdalena; Kochanowicz, Marcin; Zmojda, Jacek (Photonics Letters of Poland, 2021)
This paper presents the results of research on the luminescent properties of antimony-borate glass rods doped with europium and silver ions. The reduction of silver ions to the form of nanoparticles was carried out and the occurrence of localized plasmon resonance was demonstrated, which caused changes in the Eu3+ luminescence signal at a wavelength of 613 nm. The effect of the concentration of silver ions dopant at a constant content of europium ions on the luminescence and absorption characteristics of the produced samples was investigated. In the examined doping range, no large dependencies of spectral changes as a function of the concentration of silver ions were found. A clear quenching of the luminescence was observed due to the heating time of the doped glass matrices for the energy transition (5D0 → 7F2). Full Text: PDF References S. Kuzman, J. Perisa, V. Dordevic, I. Zekovic, I. Vukoje, Z. Antic and M. D. Dramicanin, "Surface Plasmon Enhancement of Eu3+ Emission Intensity in LaPO4/Ag Nanoparticles", Materials 13, 3071 (2020). CrossRef V.P. Prakashan, M.S. Sajna, G. Gejo, M.S. Sanu, A.C. Saritha, P.R. Biju, J. Cyriac and N.V. Unnikrishan, "Surface Plasmon Assisted Luminescence Enhancement of Ag NP/NWs-Doped SiO2-TiO2-ZrO2:Eu3+ Ternary System", Plasmonics 14, 673 (2019). CrossRef O. Malta, P. Santa-Cruz, G. Sa and F. Auzel, "Fluorescence enhancement induced by the presence of small silver particles in Eu3+ doped materials", J. Lumin., 33, 261 (1985). CrossRef O. Malta, P. Santa-Cruz, G. Sa and F. Auzel, "Time evolution of the decay of the 5Do level of Eu3+ in glass materials doped with small silver particles", Chem. Phys. Lett, 116, 396 (1985). CrossRef J. Zmojda, M. Kochanowicz, P. Miluski et al., "The influence of Ag content and annealing time on structural and optical properties of SGS antimony-germanate glass doped with Er3+ ions", Journal of Molecular Structure 1160, 428 (2018). CrossRef Ki Young Kim, Plasmonics: Principles and Applications (Croatia, InTechOpen 2012) CrossRef M.R. Dousti, M.R. Sahar, S.K. Ghoshal et al., "Up-conversion enhancement in Er3 +-Ag co-doped zinc tellurite glass: Effect of heat treatment", Journal of Non-Crystalline Solids 358, 2939 (2012). CrossRef I. Soltani, S. Hraiech, K. Horchani-Naifer et al., "Effect of silver nanoparticles on spectroscopic properties of Er3+ doped phosphate glass", Optical Materials 46, 454 (2015). CrossRef R. Schneider, E.A. de Campos, J.B.S. Mendes, J.F. Felix, P.A. Santa-Cruz, "Lead–germanate glasses: an easy growth process for silver nanoparticles and their promising applications in photonics and catalysis", RSC Advances 7 (66), 41479 (2017). CrossRef